Carrier transport in low-dimensional nanoelectronic devices : : doctoral thesis - Poljak, Mirko (M. Poljak ; Fakultet elektrotehnike i računarstva, 2013)
ABSTRACTS: This dissertation explores the consequences of low dimensionality and using new channel materials on the performance of future nanoelectronic devices. The focus is on carrier transport since its properties determine the performance gains offered by the proposed technologies. By using the semiclassical mobility modeling and atomistic quantum transport modeling based on the non-equilibrium Green's function (NEGF) formalism, the impact of the downscaling of device size on the transport properties of ultra-thin body (UTB) silicon-oninsulator (SOI), FinFET, UTB indium-gallium-arsenide-on-insulator (InGaAs-OI), and graphene-based electron devices is studied. It is found that a direct consequence of low dimensionality of UTB SOI and FinFET devices is the existence of optimum body thicknesses for which the optimum performance or minimum circuit layout area can be achieved. Similarly, a range of body thicknesses is found for which the InGaAs-OI technology is superior to SOI in terms of electron mobility and intrinsic delay time. The investigation of graphene nanoribbons (GNRs) has revealed that the optimum substrate type depends on interface impurity density and GNR width, and that the variability of transport properties induced by disorder is the most severe limiter for GNR applications in nanoelectronics. -